Phylogenetik Study of Papilio Spp Butterfly Based on ND5 Genetik Sequence in In Silico - Abdu Mas'ud; Abubakar Abdullah; Chumidach Roini (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2018)
Papilio spp is one of the members Papilionidae family. The specific character is macro lepidoptera butterflies and has beautiful colour.  The distribution of butterflies is found in Indo_Australia. Papilio spp can found on Northen Maluku and Sula archipelago region. The objectif of the research is to know genetik relationship of Papilio spp based on moleculer marker of the ND5 gene mitokondrial using insilico analysis. The genetik relationship can be knowed from the phylogenetik tree construction by sequence ND5 gene mitocondial. The Sequence ND5 gene is obstained from the National Center for Biotechnology Information (NCBI) and alignment sequence for the construction phylogenetik tree using Clustal W program acces from the National Center for Biotechnology Information (NCBI) online. The phylogenetik tree showed that Papilio ulyses from Obi island and Morotai island have one ancestor (monophyletic) with Papilio ulyses telegous from Timika.